2017
DOI: 10.1038/s41598-017-06010-8
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-entangled photon pair sources based on spontaneous four wave mixing assisted by polarization mode dispersion

Abstract: Photonic-based qubits and integrated photonic circuits have enabled demonstrations of quantum information processing (QIP) that promises to transform the way in which we compute and communicate. To that end, sources of polarization-entangled photon pair states are an important enabling technology. However, such states are difficult to prepare in an integrated photonic circuit. Scalable semiconductor sources typically rely on nonlinear optical effects where polarization mode dispersion (PMD) degrades entangleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…Spontaneous four wave mixing can be an expedient. Its successful application for photon pair generation was already demonstrated, but more progress with respect to imaging applications involving UV light needs to be done.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous four wave mixing can be an expedient. Its successful application for photon pair generation was already demonstrated, but more progress with respect to imaging applications involving UV light needs to be done.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we would like to mention several review papers and overview articles covering topics that are touched on here but are beyond the scope of this review: single photon sources and detectors, integrated‐optical sources of entangled photons, and generation of photon pairs via spontaneous four wave mixing …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GaAs possess one of the highest second-order nonlinearity (d 36 ≈ 170 pm/V at 1 µm 27 ) and a very strong Kerr coefficient n 2 ≈ 1.6 × 10 −17 m 2 W -1 at 1.5 µm 52 . Therefore, both SPDC 65 and SFWM 66 processes could be used to generate photon-pairs in GaAs/AlGaAs waveguides, making it a very versatile platform. The mature laser diode technology on III-V semiconductor platform could also be exploited to build monolithic electrically injected photon-pair sources 67 .…”
Section: Iii-v Semiconductorsmentioning
confidence: 99%
“…SFWM-based photon pair generation was also investigated in channel waveguides made with III-V semiconductors since they also possess large Kerr coefficients. Correlated photon pairs 202 and subsequently polarization-entangled states 66 were demonstrated in dispersion engineered AlGaAs waveguides exploiting their strong third-order nonlinearity.…”
Section: Channel Waveguidesmentioning
confidence: 99%
“…In 2017 Kultavewuti et al [50] demonstrated a SFWM polarization EP source implemented in an AlGaAs waveguide. This source reported CHSH violations >2.6 and a maximum fidelity of 0.92±0.01.…”
Section: Fwm Sources and Spectral Propertiesmentioning
confidence: 99%